Efficacy of different Conidial concentrations, fungal Filtrations and silver nanoparticles Mycosynthesis using two isolates of Metarhizium anisoplae against Two Stored-grain Insects - Battol Qasem Kteo; Akram Ali Mohammed; Hanaa H. Al-Saffar (Kufa Journal for Agricultural Sciences)
The current study examined the effectiveness of conidial concentration, fungal filtrate of M. anisoplae, and biologically manufactured silver nanoparticles in preventing infection by the rust-red flour beetle and the hairy grain beetle in flour sacks and jute bags. One commercial and one local M. anisoplae isolates were utilized. The synthesized silver nano-particles were characterized using, UV-vis spectrophotometer, Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM) and Atomic Force Microscope (AFM) analysis. The size of the nanoparticles ranged between (37.22 - 75.93) nm for local fungus, with an average of 53.82 nm, and (6.176 - 22.25) nm for commercial fungus, with an average of 12.372 nm. The efficiency of three types of treatments for local and commercial isolates was evaluated: conidial suspension (1×108 conidia/ml), fungal filtrate (100%), and silver nanoparticles (20%). The results demonstrated that the silver nanoparticle treatment outperformed the other treatments in providing protection against infection with T. castaneum and T. granarium after an 8-week storage period, with averages of 26.7-36 insects/bag and 47.7-66 insects/bag. The number of individual insects per bag in the remaining treatments was significantly higher than the silver nanoparticle treatment. In the control treatment, the insect densities were 366.7 and 586 insects/bag, respectively. This research indicates persuasively that biologically manufactured silver nanoparticles can be employed as a biological control agent in the treatment of grain bags and their products. It was resistant to both the rust-red flour beetle and the hairy grain beetle, which commonly infect stored products.